Preparation method of quasi-spherical nanometer yttrium oxide

CN122957869APending Publication Date: 2026-10-23江西明达功能材料有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611333121.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-23

AI Technical Summary

Benefits of technology

[0014]本发明制备的类球形纳米氧化钇电镜粒度小于500 nm,颗粒形貌为类球形,粉体粒度均匀,流动性好。本发明制备方法工艺简单、对设备要求低,生产成本低,生产过程控制方便易实现,适宜工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957869A_ABST
    Figure CN122957869A_ABST
Patent Text Reader

Abstract

A preparation method of spherical-like nano yttrium oxide, under stirring, ammonium bicarbonate-ammonia mixed solution is added into yttrium chloride solution to adjust pH to 6.5-7.5, the prepared solution is added into a certain amount of ammonium oxalate solution for precipitation, the obtained precipitate is filtered, washed, dried and calcined to obtain spherical-like nano yttrium oxide. The process control is simple, the requirement for equipment is low, the reaction condition is mild, and no new impurities are introduced in the preparation process. The obtained spherical-like nano yttrium oxide has a particle size less than 500 nm, and the particle morphology is spherical-like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing spherical nano-yttrium oxide, belonging to the field of rare earth powder materials technology. Background Technology

[0002] Yttrium oxide (Y₂O₃) is the most stable oxide form of the rare earth element yttrium and the first rare earth compound discovered by humankind, its discovery itself being a significant chapter in the history of science. When this traditional material is applied to the nanoscale, its performance boundaries are greatly expanded, spurring revolutionary applications in numerous fields, from advanced ceramics to new energy sources. Yttrium oxide is a high-melting-point (approximately 2410°C), high-density white powder with stable chemical properties; it is insoluble in water but soluble in acids. In traditional fields, it is a key raw material for manufacturing microwave magnetic materials (such as yttrium iron garnet, YIG), optical glass, ceramic additives, and high-brightness phosphors.

[0003] The micron-sized particle size of ordinary yttrium oxide limits its surface activity. When the particle size enters the nanoscale (typically 1-100 nanometers), its specific surface area increases exponentially, and the number of surface atoms surges, leading to significant surface and quantum size effects. This allows nano-yttrium oxide (nano-Y₂O₃) to possess stronger optical, electrical, magnetic, and chemical properties while retaining its high melting point and high stability. For example, its reflectivity in the near-infrared region can reach approximately 90%. In structural ceramics, adding nano-yttrium oxide (such as silicon nitride containing 6% nano-Y₂O₃ and 2% Al) can serve as a sintering aid and stabilizer, significantly improving the material's density, high-temperature strength, and toughness, making it suitable for developing high-temperature structural components such as engine parts. In the field of electronic ceramics, it is a key dopant in the manufacture of high-performance multilayer ceramic capacitors (MLCCs), improving device reliability and capacitance. Adding a small amount of nano-yttrium oxide to steel and non-ferrous alloys can significantly refine grains and enhance dispersion. For example, adding 0.5%-4% nano-Y₂O₃ to FeCr alloys can significantly enhance the alloy's oxidation resistance, ductility, and high-temperature creep resistance. Adding it to Al-Zr and copper alloys can improve conductivity and mechanical strength, making it widely used in wires, cables, and aerospace structural components. High-temperature proton-conducting materials containing a high proportion (e.g., 90%) of nano-Y₂O₃ are key components of solid oxide fuel cells (SOFCs) and electrolyzers, significantly contributing to improved energy conversion efficiency. Furthermore, it has been studied for its potential to improve the spectral conversion efficiency of solar cells.

[0004] The preparation process directly determines the particle size, morphology, and dispersibility of nano-yttrium oxide. A common preparation method is precipitation, which uses yttrium chloride as a raw material, precipitates it through carbonate or oxalate precipitation, and then calcines it at high temperature to obtain the product. Studies have shown that by controlling the Y... 3+Parameters such as concentration, precipitant ratio, temperature, and stirring speed can effectively control the precursor morphology. For example, using sodium carbonate and sodium bicarbonate as precipitants, in a positive feed method and Y... 3+ At a concentration of 0.1 mol / L and a precipitation temperature of 30℃, nano-Y₂O₃ with a D50 of 50 nm and good dispersibility can be obtained. However, this introduces sodium ions as impurities, and the precipitate has poor filterability, making it prone to agglomeration during subsequent calcination processes. While techniques such as plasma gas-phase combustion can produce high-purity nanoparticles with a purity exceeding 99.9%, a particle size of 20-30 nm, and uniform distribution, industrialization is difficult due to the complexity of equipment operation and control.

[0005] The above methods suffer from various drawbacks, including the introduction of impurities, easy agglomeration, and complex equipment, which affect the industrial preparation and downstream applications of nano-yttrium oxide. While the common oxalic acid precipitation method yields easily filtration and washing of the precipitate, the high acidity of the precipitation system causes the precipitate particles to easily "grow," making it impossible to prepare nanoscale powders. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a method for preparing near-spherical yttrium oxide nanoparticles. The process is simple and operates under mild conditions, guiding industrial production. The prepared yttrium oxide particles are near-spherical under electron microscopy, with a particle size less than 500 nm, exhibiting good flowability. This method is suitable for structural and functional ceramics, showing broad application prospects. This invention is achieved through the following technical solution.

[0007] A method for preparing spherical yttrium oxide nanoparticles involves adding an ammonium bicarbonate-ammonia solution to a yttrium chloride solution under stirring to adjust the pH to 6.5-7.5. The pH-adjusted solution is then added to a certain amount of ammonium oxalate solution to precipitate the precipitate. The precipitate is then filtered, washed, dried, and calcined to obtain spherical yttrium oxide nanoparticles.

[0008] Preferably, the concentration of the ammonium bicarbonate-ammonia solution is 5-20 g / L (based on ammonium bicarbonate), and the molar ratio of ammonium bicarbonate to ammonia is NH4HCO3:NH3·H2O = (2.0-3.5):1. This avoids excessively high local concentrations and agglomeration during pH adjustment. The feeding rate of the ammonium bicarbonate-ammonia solution needs to be controlled, preferably 5-10 ml / min, to ensure that the local concentration is not too high and forms precipitate "flocs". The role of adjusting the pH of the mixed solution is to initially form a large number of fine crystal nuclei and maintain good dispersibility. At the same time, the system pH is close to neutral, so that the particles are not easily "grown" during the subsequent oxalate conversion.

[0009] Preferably, the concentration of yttrium chloride solution is 80-100 g / L, and the free acidity of the solution, expressed as hydrogen ion concentration, is 0.05-0.2 mol / L. This facilitates pH adjustment and precise control of the precipitant dosage.

[0010] Preferably, the concentration of the ammonium oxalate solution is 50-80 g / L, and the amount of ammonium oxalate used is in a molar ratio of (3.5-5):1 to the desired yttrium oxide precipitate. Ammonium oxalate is a salt of a strong acid and a weak base; its aqueous solution is weakly acidic, with a pH of approximately 6-7, having minimal impact on the overall acidity of the precipitation system, thus preventing the precipitate particles from easily growing. Controlling the amount of ammonium oxalate converts the yttrium carbonate particles into yttrium oxalate, making the precipitate easier to filter and wash, and preventing agglomeration during calcination. Preferably, the feeding rate of the feed solution into the ammonium oxalate solution is 30-50 ml / min.

[0011] The stirring process has a certain impact on particle dispersion. When adjusting the pH of yttrium chloride solution, the stirring should be moderate to avoid agglomeration and "gelatinization" (becoming a paste-like state). The preferred stirring speed is 100-500 r / min. However, the ammonium oxalate precipitation process should be stirred rapidly to enable the particles to transform and disperse quickly. The preferred stirring speed is 500-1500 r / min.

[0012] Adding nonionic surfactants to ammonium oxalate solutions can better maintain the dispersibility of precipitated particles and further reduce agglomeration. Preferred nonionic surfactants include one or more of PEG2000, PEG4000, PEG6000, octyl glucoside, decyl glucoside, and dodecyl glucoside. These nonionic surfactants have good water solubility and can be used alone or mixed in any proportion without significant difference in effect.

[0013] Drying the precipitate before calcination can significantly reduce powder agglomeration. The preferred drying temperature is 60-80℃ for 2-6 hours. The calcination process has some impact on particle agglomeration. A programmed temperature rise is preferred, starting from room temperature to 450-550℃ over 2-4 hours, holding for 1-6 hours, then rising from 450-550℃ to 800-880℃ over 1-3 hours, holding for 2-4 hours. This can significantly reduce powder agglomeration.

[0014] The spherical yttrium oxide nanoparticles prepared by this invention have an electron microscopy particle size of less than 500 nm, exhibiting a spherical morphology, uniform particle size, and good flowability. The preparation method of this invention is simple, requires minimal equipment, has low production costs, and is easy to control, making it suitable for industrial production. Attached Figure Description

[0015] Figure 1 This is a scanning electron microscope image of the product from Example 1.

[0016] Figure 2 This is a scanning electron microscope image of the product from Example 2.

[0017] Figure 3 This is a scanning electron microscope image of the product from Example 3.

[0018] Figure 4 This is a scanning electron microscope image of the product from Example 4.

[0019] Figure 5 This is a scanning electron microscope image of the product from Example 5.

[0020] Figure 6 This is a scanning electron microscope image of the product from Example 6.

[0021] Figure 7 This is a scanning electron microscope image of the product from Example 7.

[0022] Figure 8 This is a scanning electron microscope image of the product from Example 8.

[0023] Figure 9 This is a scanning electron microscope image of the product from Example 9.

[0024] Figure 10 This is a scanning electron microscope image of the product from Example 10. Implementation

[0025] A method for preparing spherical yttrium oxide nanoparticles involves adjusting the pH to 6.5-7.5 by adding an ammonium bicarbonate-ammonia solution with a concentration of 80-100 g / L and a hydrogen ion concentration of 0.05-0.2 mol / L to a yttrium chloride solution at a stirring speed of 100-500 r / min. Then, under stirring at 500-1500 r / min, the pH-adjusted yttrium chloride solution is added to a certain amount of ammonium oxalate solution with a concentration of 50-80 g / L to precipitate the precipitate. The precipitate is washed, filtered, vacuum dried, and calcined under programmed temperature control to obtain spherical yttrium oxide nanoparticles. The ammonium bicarbonate-ammonia solution has a concentration of 5-10% by mass of ammonium bicarbonate, and the molar ratio of ammonium bicarbonate to ammonia is NH4HCO3:NH3·2. H₂O = (2.0-3.5):1; the amount of ammonium oxalate used is based on a molar ratio of ammonium oxalate to the desired yttrium oxide precipitate of (3.5-5):1. Surfactants that can be added to the ammonium oxalate include at least one of PEG2000, PEG4000, PEG6000, octyl glucoside, decyl glucoside, and dodecyl glucoside. The precipitate produced during the preparation process of this invention is easily washed and filtered. The prepared yttrium oxide powder has an electron microscopy particle size of less than 500 nm, a near-spherical morphology, uniform particle size, and good flowability. Specific embodiments are as follows. Example

[0026] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 80 g / L, H+). +=0.1 mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 5%, molar ratio NH4HCO3:NH3·H2O=3.5:1) to yttrium chloride solution at a stirring speed of 500 r / min at a rate of 10 ml / min, adjust pH=6.5, and set aside; Precipitation: At room temperature and with a stirring speed of 1500 r / min, yttrium chloride solution with adjusted pH was added to 961 ml of ammonium oxalate solution with a concentration of approximately 80 g / L (molar ratio of ammonium oxalate:REO = 3.5:1) at a rate of 30 ml / L. After precipitation, the solution was washed and filtered. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 60℃ for 6 h. It was then placed in a high-temperature furnace, and the temperature was slowly increased from room temperature to 550℃ over 4 h, held at 550℃ for 1 h, and then increased to 880℃ over 3 h, held for 2 h, and finally cooled naturally to obtain 39.2 g of yttrium oxide powder. Electron microscopy revealed that the powder morphology was spherical, with a microscopic particle size less than 100 nm (see appendix). Figure 1 ). Example

[0027] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 90 g / L, H+). + =0.05mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 10%, molar ratio NH4HCO3:NH3·H2O=2.5:1) to yttrium chloride solution at a stirring speed of 100 r / min at a rate of 5 ml / min, adjust pH=7.5, and set aside; Precipitation: Prepare 1647 ml of ammonium oxalate solution with a concentration of approximately 60 g / L (molar ratio of ammonium oxalate:REO = 4:1). Weigh out surfactant PEG-2000 at 2% of the mass of yttrium oxide and dissolve it in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a rate of 50 ml / L at room temperature while stirring at 1000 r / min to precipitate the oxalate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 80℃ for 4 h. It was then removed and placed in a high-temperature furnace, where the temperature was slowly increased from room temperature to 450℃ over 4 h, held at 450℃ for 4 h, then increased to 800℃ over 1 h, held for 4 h, and finally cooled naturally to obtain 44.2 g of yttrium oxide powder. Electron microscopy revealed that the powder morphology was spherical with a microscopic particle size less than 200 nm (see appendix). Figure 2 ). Example

[0028] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 100 g / L, H+). +=0.2mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 6%, molar ratio NH4HCO3:NH3·H2O=3:1) to yttrium chloride solution at a stirring speed of 400 r / min at a rate of 5 ml / min, adjust pH=7, and set aside; Precipitation: Prepare 2470 ml of ammonium oxalate solution (molar ratio of ammonium oxalate:REO = 4.5:1) with approximately 5% (by mass) of yttrium oxide. Weigh out surfactant PEG-4000 and dissolve it in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a stirring speed of 800 r / min at room temperature at a rate of 40 ml / L to precipitate the oxalate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 70℃ for 4 h. It was then removed and placed in a high-temperature furnace, where the temperature was slowly increased from room temperature to 500℃ over 2 h, held at 500℃ for 2 h, and then increased to 850℃ over another 2 h, held for 2 h, and finally cooled naturally to obtain 49.2 g of yttrium oxide powder. Electron microscopy revealed that the powder morphology was spherical, with a microscopic particle size less than 300 nm (see appendix). Figure 3 ). Example

[0029] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 80 g / L, H+). + =0.15mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 8%, molar ratio NH4HCO3:NH3·H2O=2:1) ​​to yttrium chloride solution at a stirring speed of 300r / min at a rate of 8 ml / min, adjust pH=6.5, and set aside; Precipitation: Prepare 1370 ml of ammonium oxalate solution with a concentration of approximately 80 g / L (molar ratio of ammonium oxalate:REO = 5:1). Weigh out surfactant PEG-6000 at 8% of the mass of yttrium oxide and dissolve it in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a rate of 35 ml / L at room temperature while stirring at 1000 r / min to precipitate the oxalate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 60℃ for 8 h. After cooling, it was placed in a high-temperature furnace and slowly heated from room temperature to 500℃ over 3 h, held at 500℃ for 6 h, then heated to 820℃ over 2 h, held at 820℃ for 3 h, and finally cooled naturally to obtain 39.4 g of yttrium oxide powder. Electron microscopy showed that the powder morphology was spherical with a microscopic particle size of less than 400 nm (see appendix). Figure 4 ). Example

[0030] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 100 g / L, H+). + =0.2mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 5%, molar ratio NH4HCO3:NH3·H2O=3:1) to yttrium chloride solution at a stirring speed of 500 r / min at a rate of 5 ml / min, adjust pH=7, and set aside; Precipitation: Prepare 1920 ml of ammonium oxalate solution with a concentration of approximately 50 g / L (molar ratio of ammonium oxalate:REO = 3.5:1). Weigh out 10% of the mass of yttrium oxide and dissolve the surfactant octyl glucoside in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a rate of 30 ml / L at room temperature while stirring at 500 r / min to precipitate the oxalate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 65°C for 5 hours. It was then removed and placed in a high-temperature furnace, where the temperature was slowly increased from room temperature to 550°C over 4 hours, held at 550°C for 4 hours, then increased to 850°C over another 2 hours, held for 2 hours, and finally cooled naturally to obtain 49 g of yttrium oxide powder. Electron microscopy revealed that the powder morphology was spherical, with a microscopic particle size of approximately 70 nm (see attached image). Figure 5 ). Example

[0031] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 90 g / L, H+). + =0.1mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 8%, molar ratio NH4HCO3:NH3·H2O=3.5:1) to yttrium chloride solution at a stirring speed of 500 r / min at a rate of 5 ml / min, adjust pH=7.5, and set aside; Precipitation: Prepare 1235 ml of ammonium oxalate solution with a concentration of approximately 70 g / L (molar ratio of ammonium oxalate:REO = 3.5:1). Weigh out decyl glucoside, a surfactant, at 5% of the mass of yttrium oxide, and dissolve it in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a stirring speed of 1200 r / min at room temperature at a rate of 50 ml / L to precipitate the oxalate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 80℃ for 4 h. After cooling, it was placed in a high-temperature furnace and slowly heated from room temperature to 500℃ over 3 h, held at 500℃ for 3 h, then heated to 880℃ over another 3 h, held for 2 h, and finally cooled naturally to obtain 44 g of yttrium oxide powder. Electron microscopy showed that the powder morphology was spherical with a microscopic particle size of approximately 200 nm (see appendix). Figure 6 ). Example

[0032] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 80 g / L, H+). + =0.08mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 6%, molar ratio NH4HCO3:NH3·H2O=2:1) ​​to yttrium chloride solution at a stirring speed of 100 r / min at a rate of 10 ml / min, adjust pH=6.5, and set aside; Precipitation: Prepare 1460 ml of ammonium oxalate solution with a concentration of approximately 60 g / L (molar ratio of ammonium oxalate:REO = 4:1). Weigh out 2% (by mass) of the surfactant dodecyl glucoside and dissolve it in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a rate of 45 ml / L at room temperature while stirring at 800 r / min to precipitate the oxalate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 70℃ for 6 hours. After cooling, it was placed in a high-temperature furnace and slowly heated from room temperature to 550℃ over 2 hours. The temperature was then maintained at 550℃ for 5 hours, followed by a further heating over 2 hours to 800℃, which was maintained for 4 hours. Finally, it was allowed to cool naturally to obtain 39.28 g of yttrium oxide powder. Electron microscopy revealed that the powder morphology was quasi-spherical with a microscopic particle size less than 500 nm (see appendix). Figure 7 ). Example

[0033] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 100 g / L, H+). + =0.2mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 10%, molar ratio NH4HCO3:NH3·H2O=2.5:1) to yttrium chloride solution at a stirring speed of 200 r / min at a rate of 5 ml / min, adjust pH=7.5, and set aside; Precipitation: Prepare 1300 ml of ammonium oxalate solution with a concentration of approximately 80 g / L (molar ratio of ammonium oxalate to REO = 3.8:1). Weigh out surfactant PEG-6000 and dodecyl glucoside (mass ratio of PEG-6000 to dodecyl glucoside = 1:1) at 6% of the mass of yttrium oxide and dissolve them in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a stirring speed of 1000 r / min at room temperature at a rate of 30 ml / L to precipitate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 60℃ for 8 hours. After cooling, it was placed in a high-temperature furnace and slowly heated from room temperature to 450℃ over 4 hours. The temperature was held at 450℃ for 2 hours, then increased to 850℃ over 3 hours and held for 3 hours. Finally, it was allowed to cool naturally to obtain 49.1 g of yttrium oxide powder. Electron microscopy revealed that the powder morphology was spherical with a microscopic particle size of approximately 300 nm (see appendix). Figure 8 ). Example

[0034] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 90 g / L, H+). + =0.15 mol / L), and with a stirring speed of 300 r / min, add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 8%, molar ratio NH4HCO3:NH3·H2O=3.5:1) to the yttrium chloride solution at a rate of 8 ml / min, adjust the pH to 7.2, and set aside; Precipitation: Prepare 1480 ml of ammonium oxalate solution with a concentration of approximately 70 g / L (molar ratio of ammonium oxalate:REO = 4.2:1). Weigh out surfactant PEG-6000, octyl glucoside, and dodecyl glucoside (mass ratio of PEG-6000:octyl glucoside:dodecyl glucoside = 1:1:1) at 8% of the mass of yttrium oxide and dissolve them in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a stirring speed of 900 r / min at room temperature at a rate of 35 ml / L to precipitate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 70℃ for 5 hours. After cooling, it was placed in a high-temperature furnace and slowly heated from room temperature to 550℃ over 3 hours. The temperature was then maintained at 550℃ for 6 hours, followed by a further heating to 820℃ over 1 hour, and maintained for 2 hours. Finally, it was allowed to cool naturally to obtain 44.2 g of yttrium oxide powder. Electron microscopy revealed that the powder morphology was spherical with a microscopic particle size of approximately 250 nm (see appendix). Figure 9 ). Example

[0035] Adjust pH: Take 500 ml of yttrium chloride solution (REO concentration 80 g / L, H+). + =0.05 mol / L), add ammonium bicarbonate-ammonia water mixed solution (ammonium bicarbonate concentration 6%, molar ratio NH4HCO3:NH3·H2O=3:1) to yttrium chloride solution at a stirring speed of 400 r / min at a rate of 6 ml / min, adjust pH=7, and set aside; Precipitation: Prepare 1830 ml of ammonium oxalate solution with a concentration of approximately 60 g / L (molar ratio of ammonium oxalate:REO = 5:1). Weigh out surfactants PEG-2000, PEG-6000, octyl glucoside, and dodecyl glucoside (mass ratio of PEG-2000:PEG-6000:octyl glucoside:dodecyl glucoside = 1:1:1:1) at 10% of the mass of yttrium oxide and dissolve them in the ammonium oxalate solution. Add the pH-adjusted yttrium chloride solution to the ammonium oxalate solution at a stirring speed of 1200 r / min at room temperature at a rate of 50 ml / L to precipitate the oxalate. After precipitation, wash and filter. Drying and calcination: The washed and filtered precipitate was placed in a drying oven and dried at 75℃ for 8 h. After cooling, it was placed in a high-temperature furnace and slowly heated from room temperature to 500℃ over 2 h, held at 500℃ for 3 h, then heated to 880℃ over another 3 h, held for 2 h, and finally cooled naturally to obtain 39.6 g of yttrium oxide powder. Electron microscopy showed that the powder morphology was spherical with a microscopic particle size of approximately 50 nm (see appendix). Figure 10 ).

[0036] The above are merely preferred embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for preparing spherical yttrium oxide nanoparticles, characterized in that, Under stirring condition one, an ammonium bicarbonate-ammonia solution was added to the yttrium chloride solution to adjust the pH to 6.5-7.

5. Under stirring condition two, the pH-adjusted yttrium chloride solution was added to a certain amount of ammonium oxalate solution to precipitate. The precipitate was washed, filtered, dried, and calcined to obtain spherical nano-yttrium oxide.

2. The preparation method according to claim 1, characterized in that, The ammonium bicarbonate-ammonia solution has a concentration of 5-10% by mass of ammonium bicarbonate, and the molar ratio of ammonium bicarbonate to ammonia is NH4HCO3:NH3·H2O = (2.0-3.5):

1.

3. The preparation method according to claim 2, characterized in that, The feeding rate of the ammonium bicarbonate-ammonia solution is 5-10 ml / min.

4. The preparation method according to claim 1, characterized in that, The first stirring state has a rotation speed of 100-500 r / min, and the second stirring state has a rotation speed of 500-1500 r / min.

5. The preparation method according to claim 1, characterized in that, The concentration of the yttrium chloride solution is 80-100 g / L.

6. The preparation method according to claim 5, characterized in that, The hydrogen ion concentration in the yttrium chloride solution is 0.05-0.2 mol / L.

7. The preparation method according to claim 1, characterized in that, The concentration of the ammonium oxalate solution is 50-80 g / L, and the amount of ammonium oxalate used is based on the molar ratio of ammonium oxalate to the required yttrium oxide precipitate as (3.5-5):

1.

8. The preparation method according to claim 1, characterized in that, The feeding rate of the feed solution into the ammonium oxalate solution is 30-50 ml / min.

9. The preparation method according to claim 1, characterized in that, A nonionic surfactant was added to the ammonium oxalate solution.

10. The preparation method according to claim 9, characterized in that, The nonionic surfactant is at least one of polyethylene glycol and alkyl glycosides.

11. The preparation method according to claim 10, characterized in that, The polyethylene glycol nonionic surfactants include PEG2000, PEG4000, and PEG6000.

12. The preparation method according to claim 10, characterized in that, The alkyl glycoside nonionic surfactants include octyl glucoside, decyl glucoside, and dodecyl glucoside.

13. The preparation method according to any one of claims 9-12, characterized in that, The amount of the nonionic surfactant added is 2-10% (by weight) of the REO content of the yttrium chloride solution.

14. The preparation method according to claim 1, characterized in that, The drying process is carried out at a temperature of 60-80℃ for 4-8 hours.

15. The preparation method according to claim 1, characterized in that, The calcination process employs a programmed temperature increase, raising the temperature from room temperature to 450-550℃ in 2-4 hours, holding the temperature for 1-6 hours, and then raising the temperature from 450-550℃ to 800-880℃ in 1-3 hours, holding the temperature for 2-4 hours.

16. The preparation method according to claim 1, characterized in that, The spherical yttrium oxide nanoparticles have an electron microscopy particle size of less than 500 nm and a morphology of spherical shape.